Istifhām in the Phrase Mā Khaṭbu in the Qur’an - Ramdana Nur; M. Ghalib M; Abdul Ghany; Muhammad Arwin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This article examines the use of the istifhām phrase Mā Khaṭbu in the Qur'an. This phrase consists of the word “mā,” which means “what,” and “khaṭb,” which refers to a major event or important matter. The method used is a qualitative approach with thematic analysis of the verses containing the phrase Mā Khaṭbu. The results of the study indicate that the phrase Mā Khaṭbu serves more than just a question to obtain an answer. This phrase is used as a rhetorical tool aimed at arousing the moral and spiritual awareness of readers, as well as encouraging deep reflection and introspection. Additionally, this phrase also functions as social criticism and satire toward certain attitudes or conditions that require attention. Academically, this research contributes to the study of balaghah, tafsir, and Qur’anic linguistics. This research also enriches understanding of the use of rhetorical questions as a spiritual educational method that can shape the inner consciousness of Muslims.